2014
DOI: 10.1177/0018720814546531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carrying a Backpack in an Asymmetrical Manner on the Asymmetries of the Trunk and Parameters Defining Lateral Flexion of the Spine

Abstract: We suggest that the issue of safe backpack weight be reassessed and that students be taught basic ergonomic principles on how to carry loads. Changes to the management pattern of carrying textbooks to and from school also should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
1
14
0
4
Order By: Relevance
“…Regarding method of carrying school bag, the present study showed that carrying school bag on one shoulder or by one hand increases the risk of suffering from back pain by about four times than students' carrying school bags on both shoulders. This finding was in accordance with the findings from review studies that showed carrying school bag on one shoulder, or by one hand causes asymmetry in muscle activity and encourages lateral spinal bending and might lead to changes in shoulder level and development of shoulder, neck and lower back pain even if the bag weight constitutes 10% of the child's weight [45,47]. Similarly, a study conducted among Egyptian school girls aged from 6-14 years and found that way of carriage bag had associated with girls back pain.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding method of carrying school bag, the present study showed that carrying school bag on one shoulder or by one hand increases the risk of suffering from back pain by about four times than students' carrying school bags on both shoulders. This finding was in accordance with the findings from review studies that showed carrying school bag on one shoulder, or by one hand causes asymmetry in muscle activity and encourages lateral spinal bending and might lead to changes in shoulder level and development of shoulder, neck and lower back pain even if the bag weight constitutes 10% of the child's weight [45,47]. Similarly, a study conducted among Egyptian school girls aged from 6-14 years and found that way of carriage bag had associated with girls back pain.…”
Section: Discussionsupporting
confidence: 91%
“…The collected ideas were gathered in an experience board using materials and photos, as a first move towards material expressions [3]. The main discoveries during these sessions: that backpacks often slide and are displaced due to human motion, and that an asymmetrical distribution of the weight often leads to pain, correlate with [6]. Over the course of the study we developed two prototypes, which we evaluated through walking and hiking.…”
Section: Methodsmentioning
confidence: 99%
“…Over time, a hiker's pack can easily go out of alignment. According to a prior study, asymmetrical or misaligned backpacks are a significant cause of back pain [6]-an issue for novice hikers who cannot recognise shifts in their pack's alignment. We present Sensepack, a prototype wearable sensor that sits inbetween the body and the backpack.…”
Section: Introductionmentioning
confidence: 99%
“…W Polsce donoszono już o zbyt ciężkich tornistrach uczniów w szkołach podstawowych [3,[15][16][17]. Rozwiązaniem tego problemu miała być zmiana legislacyjna nakazująca udostępnienie uczniom szafek na terenie szkoły.…”
Section: Wstępunclassified
“…Sytuacja dzieci wczesnoszkolnych w Polsce wymaga wprowadzenia natychmiastowych działań regulujących zasady obciążenia tornistrami. Wyniki tego badania pokazują, że 25% uczniów nosi tornistry cięższe niż 15% m.c., [3,[15][16][17]. W 2016 r. przeprowadzono ogólnopolskie badanie 114 000 uczniów z 388 szkół podstawowych i 340 gimnazjów [20].…”
Section: Omówienieunclassified